Freezing morphologies of impact water droplets on an inclined subcooled surface - Zhu, Fangqi (2022)
Freezing of impact water droplets is ubiquitous in nature. Prior studies mostly focus on the freezing shapes of droplets impinging perpendicularly to a cold surface. In this work, we investigate how the frozen morphologies of impact water droplets are formed on a subcooled inclined (45 °) surface. To enhance the coupling between droplet impact dynamics and solidification, we hereby conduct the experiments on superhydrophilic surfaces under various substrate temperatures (-45 °C ≤ Ts ≤ -25 °C) and droplet impact velocities (1.33 m/s ≤ V0 ≤ 3.96 m/s) where the cooling rate is significantly improved. Intriguingly, we discover four types of frozen droplet morphologies, namely elliptical cap, half ring + cap Ⅰ, half ring + cap Ⅱ, and half ring + single ring, depending upon the impact velocity and substrate temperature. The formation of such morphologies resulted from the competition between the timescales associated with droplet solidification and impact hydrodynamics are appreciably altered by the inclined impact due to symmetry breaking as compared to the normal impact. To unravel the underlying physics, based on scaling analyses we propose a phase diagram to show how frozen morphologies are controlled by droplet impact and freezing related timescales, and find that such phase diagram can corroborate with the experimental findings.